Influence of the combined action of Fusarium spp. fungi and temperature on some tomatoes growth traits - G. A. Lupashku; N. I. Mihnea; S. I. Gavzer (Овощи России, 2020)
Relevance. Tomato root rot is a complex disease caused by a variety of soil-borne fungal pathogens, among which Fusarium oxysporum, F. solani and F. gibbosum occur with the greatest frequency in the conditions of the Republic of Moldova. The originality of the work consists in identifying the differentiated influence of pathogens of Fusarium root rot and temperature on the variability and heritability of the organs of growth and development of tomato plants.Material and methods. Two varieties and 3 lines of tomatoes with good economically valuable characteristics were used as material for the study. To test the response of plants to pathogens of fusarium root rot, we used culture filtrates of 6 – F. oxysporum isolates, 6 – F. solani, and 4 – F. gibbosum, prepared in a standard liquid Czapek medium. The plants were grown at the optimum temperature (23...24°C) and with alternating temperatures of 23...24°C and 10...11°C for two days each. Seed germination and root length were used as indicators of growth and development. The genetic parameters of the variability and heritability of the studied traits were studied.Results. An analysis of the reaction based on seeds germination and root growth showed its significant differentiation in the tomato genotype x type of fungus x isolate of the fungus x temperature system. A factor analysis of the interaction of the tomato genotype x Fusarium fungus revealed a significant role of the plant genotype in response to the pathogens. A significant effect of Fusarium fungi and temperature on the genetic and phenotypic variance of signs of growth and development of tomato plants, heritability in a broad sense, genotypic and phenotypic coefficient of variation, and genetic progress have been established. It is concluded that it is advisable to use the reaction of signs of growth and development of tomato to Fusarium pathogens in order to identify genotypes with good inheritance of the resistance trait.